Circulating CTRP6 Levels are Increased in Overweight or Obese Chinese Individuals and Associated with Insulin Resistance Parameters: A Pilot Study - Liao, Xin; Liu, Sha; Tang, Xuejiao; Yang, Dan; Liu, Hua; Gao, Lin; Yang, Gangyi (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims CTRP6, a newly discovered adipokine, has been found to be a regulator for energy homeostasis. However, the association between circulating CTRP6 and obesity in humans is still unclear.Methods 256 individuals, including 185 overweight/obese (OW/OB) and 71 normal weight adults, were recruited for this study. Circulating concentrations of CTRP6 and adiponectin (Adipoq) were examined by ELISA.Results Serum CTRP6 levels in obese individuals were significantly increased compared with those in healthy individuals (506.1±134.9 vs.363.3±80.5 ng/mL, P<0.01). Conversely, serum Adipoq concentrations in OW/OB individuals were markedly decreased compared with healthy controls [20.8 (12.1–29.3) vs. 14.1 ( 8.61–17.7) ; P<0.01]. Correlation analysis revealed that there was a positive relationship between circulating CTRP6 and age, BMI, Fat%, LDL-C, TG, WHR, TC, FBG, FIns, HOMA-IR and HbA1c, but there was an inverse correlation with Adipoq and HDL-C. Logistic regression analysis revealed that high serum CTRP6 levels are markedly associated with OW/OB. Finally, ROC curve analysis showed that the cut-off value for serum CTRP6 for prediction of IR is 518 ng/mL.Conclusions CTRP6 may be a marker related to OW/OB.
Keywords: Adipokine; CTRP-6; overweight/obesity; Insulin resistance